ROTARY IMPACT CAPACITY PLASTIC CRUSHER ANALYSIS MAX 35 KG/HOUR - Agus Septiana; Yudi Samantha; Haris Budiman (Jurnal Mekanika dan Manufaktur, 2021)
Plastik crusher machine is made with capacity of max 35 kg/hr, it is easy to operate. Especially can to destroy material of break Plastik containers of bottled water / wasteof Plastik. Formula and teori used are to design to crusher of Plastik, It is constructed based on standard measurement 50 x 50 x 150 cm withcapacity 35 kghr. So resulted that yield times intersection of 23 kg/hr.